2014
DOI: 10.1126/scitranslmed.3009093
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 mutations implicated in neurodegeneration impair cell surface transport and phagocytosis

Abstract: Genetic variants in the triggering receptor expressed on myeloid cells 2 (TREM2) have been linked to Nasu-Hakola disease, Alzheimer's disease (AD), Parkinson's disease, amyotrophic lateral sclerosis, frontotemporal dementia (FTD), and FTD-like syndrome without bone involvement. TREM2 is an innate immune receptor preferentially expressed by microglia and is involved in inflammation and phagocytosis. Whether and how TREM2 missense mutations affect TREM2 function is unclear. We report that missense mutations asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
858
5
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 667 publications
(928 citation statements)
references
References 49 publications
63
858
5
2
Order By: Relevance
“…Therefore, loss-of-function mutations in TREM2 may lead to unimpeded protein aggregate deposition and result in progression of the respective diseases. Indeed, missense TREM2 mutations associated with FTD and FTD-like syndrome were found to reduce TREM2 protein maturation, thereby abolishing its shedding by ADAM proteases and impairing the phagocytic activity of TREM2-expressing cells (Kleinberger, et al, 2014). However, others reported that the depletion of one allele of TREM2 in the APPPS1 mouse model did not affect Aβ deposition, even if TREM2 heterozygosity altered the microglial response in these mice (Ulrich, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, loss-of-function mutations in TREM2 may lead to unimpeded protein aggregate deposition and result in progression of the respective diseases. Indeed, missense TREM2 mutations associated with FTD and FTD-like syndrome were found to reduce TREM2 protein maturation, thereby abolishing its shedding by ADAM proteases and impairing the phagocytic activity of TREM2-expressing cells (Kleinberger, et al, 2014). However, others reported that the depletion of one allele of TREM2 in the APPPS1 mouse model did not affect Aβ deposition, even if TREM2 heterozygosity altered the microglial response in these mice (Ulrich, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of TREM2 function reduces the ability of microglia to engulf Aβ (15). AD patients with the TREM2 variant of R47H showed fewer microglia surrounding plaques, increased numbers of filamentous non-compacted plaques, and more p-tau-positive neurites around plaques (10).…”
Section: Resultsmentioning
confidence: 99%
“…Trem2 is a scavenger receptor found on the surface of myeloid cells, and TREM2 mutations leading to impaired phagocytic activity [39] are strong risk factors for multiple neurodegenerative diseases, including ALS [26,36,10].…”
Section: Discussionmentioning
confidence: 99%